A randomized Phase 2 study to compare erlotinib with or without bevacizumab in previously untreated patients with advanced non–small cell lung cancer with EGFR mutation. Issue 3 (30th November 2022) - Lee, Youngjoo; Kim, Hye Ryun; Hong, Min Hee; Lee, Ki Hyeong; Park, Keon Uk; Lee, Geon Kook; Kim, Hyae Young; Lee, Soo‐Hyun; Lim, Kun Young; Yoon, Sung Jin; Cho, Byoung Chul; Han, Ji‐Youn
Abstract: Background: This study evaluated whether an addition of bevacizumab to erlotinib improves clinical outcomes in patients with advanced EGFR ‐mutated non–small cell lung cancer (NSCLC). Methods: This is an open‐label, multicenter, randomized Phase 2 study in South Korea. Chemonaïve patients with Stage IIIB/IV NSCLC with EGFR 19 deletion or L858R mutation were eligible. Asymptomatic brain metastasis (BM) was enrolled without local treatment. Patients received either erlotinib plus bevacizumab or erlotinib. Results: Between December 2016 and March 2019, 127 patients were randomly assigned to receive erlotinib plus bevacizumab ( n  = 64) or erlotinib ( n  = 63). Fifty‐nine (46.5%) patients had baseline BM. Fewer patients in the erlotinib plus bevacizumab arm received radiotherapy for BM than in the erlotinib arm (10.3% vs. 40.0%). A trend toward longer progression‐free survival (PFS) was observed in the erlotinib plus bevacizumab arm compared with the erlotinib alone arm; however, it was not statistically significant (median PFS, 17.5 months vs. 12.4 months; hazard ratio [HR],  0.74; 95% CI, 0.51–1.08; p  = .119). The unplanned subgroup analysis showed a longer PFS with erlotinib plus bevacizumab in patients with BM (median PFS, 18.6 months vs. 10.3 months; HR,  0.54; 95% CI, 0.31–0.95; p  = .032). Grade 3 or worse adverse events occurred in 56.6% of the erlotinib plus bevacizumab arm and 20.6% of the erlotinib arm. Conclusions: Although it was not statistically significant, a trend to improvement in PFS was observed in patients with erlotinib plus bevacizumab compared to erlotinib alone. Plain Language Summary: A randomized Phase 2 study compared erlotinib with or without bevacizumab in previously untreated patients with advanced non–small cell lung cancer with EGFR mutation. The erlotinib plus bevacizumab failed to improve median progression‐free survival compared with the erlotinib alone. However, the progression‐free survival benefit from erlotinib plus bevacizumab was found in patients with brain metastasis with no severe hemorrhagic adverse effects. Abstract : A trend to improvement in progression‐free survival was observed in patients with advanced EGFR ‐mutated non–small cell lung cancer treated with erlotinib plus bevacizumab compared with erlotinib alone. The progression‐free survival benefit from erlotinib plus bevacizumab was most significant in patients with brain metastasis with no severe hemorrhagic adverse effects.